Analisis Biaya Efektif Terapi Diare Pasien Rawat Inap RS Putri Hijau Medan - Muhammad Gunawan; Suprianto; Melati Yulia Kusumastuti; Sumardi; Debi Meilani (Yayasan Penelitian dan Inovasi Sumatera, 2022)
Diarrhea is characterized by the excretion of liquid stools with a frequency of three or more times a day, due to gastrointestinal infections due to food and water contaminated with microorganisms, or directly from humans due to poor sanitation. This study was to determine the characteristics of diarrhea patients, treatment and cost-effectiveness of treatment at Putri Hijau Hospital, Medan. The non-experimental research is descriptive and retrospective in nature of financial patient medical records from July to December 2018. Cost Effectiveness Analysis as a method of cost analysis. The characteristics of the patients obtained were 14 women (46.670%) and 16 men (53.33%). The effectiveness of New Diatabs (92.30%) and New Diatabs Metronidazole (94.11%). The cost of therapy with New Diatabs is Rp. 1,547,771/patient and New Diatabs Metronidazole is Rp. 1,562,590/patient. Average cost-effectiveness New Diatabs Rp. 190,345 and New Diatabs Metronidazole Rp. 183,060, so it is concluded that the cost-effective therapy is the use of the combination of New Diatabs Metronidazole compared to New Diatabs.